Identificação de genes associados à epifisiólise proximal do fêmur por meio da análise do transcriptoma da cartilagem em frangos de corte - Hul, Ludmila Mudri (2020)
In the current poultry industry, locomotor problems are among the main ones, causing major economic losses and affecting animal welfare. Among bone disorders, the most frequent in the femur are dyschondroplasia, epiphysiolysis or separation of the femoral head and Bacterial Chondronecrosis with Osteomyelitis (BCO), also described as Femoral Head Necrosis (FHN). In the present study, the aim was to identify the differentially expressed (DE) genes in the articular cartilage between normal broilers and those affected by proximal epiphysiolysis of the femur through RNA-Seq analysis. For this, eight commercial broilers with 35 days of age, four normal and four affected with epiphysiolysis in the head of the femur were used. After RNA extraction from the articular cartilage (CA), cDNA libraries were prepared for mRNA sequencing with the Illumina platform, following a paired-end protocol. The sequences that passed the quality control in the Seqy-Clean program were mapped with the chicken reference genome (Gallus gallus, assembly GRCg6a) using the STAR tool. The DE genes between the normal and affected groups were determined using the edgeR package from R considering False Discovery Rate (FDR) ≤0.05.In the transcriptome analysis, 12,169 genes were expressed in the femoral articular cartilage. Of these, 107 genes were DE between normal and affected chickens, of which 9 were downregulated and 98 were upregulated in the affected broilers. For validation, the relative expression of 10 genes was evaluated. The total RNA of AC tissue was isolated from 10 normal and 10 epiphysiolysis-affected broilers . For the analysis of qPCR, a set of 10 constitutive genes was previously evaluated for their stability to be used as reference gene in this study. Thus, the reference genes used were RPL5 (Ribosomal Protein L5) and RPLP1 (Lateral Subunit of the Stalk Ribosomal Protein P1), the most stable genes within the tested candidates. From those 10 genes evaluated, 6 were validated: AVBD1, AVBD2, ANK1, ADA, EPX, RHAG, being upregulatedin broilers affected by epiphysiolysis. In the functional analysis, using the set of genes DE, 79 biological processes (PB) were identified in the DAVID database, being grouped into 12 macrobioprocesses with the REViGO tool. The main PB found were involved in the response to the biotic stimulus, gas transport, cell activation, catabolism of carbohydrate derivatives, regulation of multiple organisms, immune system, muscle contraction, multiple organism process, cytolysis, leukocytes, and adhesion between cells. Among the genes potentially triggering epiphysiolysis, the protein inducible by interferon-alpha 6 (IFI6), adenosine deaminase (ADA), cathelicidin-3 (CATH3), avian beta-defensin 1 (AVBD1), avian beta defense 2 (AvBD2) , ankirin 1 (ANK 1), chemotaxine derived from leukocyte cells 2 (LECT2) and collagen type XII alpha chain 1 (COL13A1) can be highlighted. In this study, the first transcriptome of the articular cartilage of chickens was generated and, thus, it was possible to identify a set of candidate genes to trigger changes in the growth plate of the femur.